Loss of PPARα function promotes epigenetic dysregulation of lipid homeostasis driving ferroptosis and pyroptosis lipotoxicity in metabolic dysfunction associated Steatotic liver disease (MASLD) - Theys, Claudia; Vanderhaeghen, Tineke; Van Dijck, Evelien; Peleman, Cedric; Scheepers, Anne; Ibrahim, Joe; Mateiu, Ligia; Timmermans, Steven; Vanden Berghe, Tom; Francque, Sven M.; Van Hul, Wim; Libert, Claude; et al. (Frontiers in Molecular Medicine, 2024)
Metabolic Dysfunction Associated Steatotic Liver Disease (MASLD) is a growing epidemic with an estimated prevalence of 20%–30% in Europe and the most common cause of chronic liver disease worldwide. The onset and progression of MASLD are orchestrated by an interplay of the metabolic environment with genetic and epigenetic factors. Emerging evidence suggests altered DNA methylation pattern as a major determinant of MASLD pathogenesis coinciding with progressive DNA hypermethylation and gene silencing of the liver-specific nuclear receptor PPARα, a key regulator of lipid metabolism. To investigate how PPARα loss of function contributes to epigenetic dysregulation in MASLD pathology, we studied DNA methylation changes in liver biopsies of WT and hepatocyte-specific PPARα KO mice, following a 6-week CDAHFD (choline-deficient, L-amino acid-defined, high-fat diet) or chow diet. Interestingly, genetic loss of PPARα function in hepatocyte-specific KO mice could be phenocopied by a 6-week CDAHFD diet in WT mice which promotes epigenetic silencing of PPARα function via DNA hypermethylation, similar to MASLD pathology. Remarkably, genetic and lipid diet-induced loss of PPARα function triggers compensatory activation of multiple lipid sensing transcription factors and epigenetic writer-eraser-reader proteins, which promotes the epigenetic transition from lipid metabolic stress towards ferroptosis and pyroptosis lipid hepatoxicity pathways associated with advanced MASLD. In conclusion, we show that PPARα function is essential to support lipid homeostasis and to suppress the epigenetic progression of ferroptosis-pyroptosis lipid damage associated pathways towards MASLD fibrosis.